Strategic Implementation on the Lean Management Approach in Human Resource Practices: Lean Management Methodology - Al-Mahrooqi, Nusaiba (Advances in Social Sciences Research Journal, 2022)
At present, the competitive advantage is an important basis for the organization to achieve main objective. The global economic environment and results also provides opportunity in implementing a successful strategy, which affects their survival in the market, whether in local or global market. The aim of this study is to investigate the effective strategies to improve the services of different operations in the Human Resource by using lean management approach. The problems identified in this study are mainly on the bottlenecks, minimizing the waste activities and how to add value to the services. The study has identified the success factors that could help the human resource department to improve the operation and digital transformation. The main findings of the research will address the wastages in the HR processes. The outcome of this study was based on the literature that implemented the KPI, which witnessed the effect of success with strategic implementation of lean management. Ultimately, this study argues for the creation of an “umbrella” software related to HR process for further improvisations. There’s also recommendation to identify a staff from the team who possesses leadership characteristics in effectively implementing lean management.